Perkembangan Kreativitas, Bakat, dan Motivasi Anak Sekolah Dasar - Tillah, Mardha; Neviyarni, Neviyarni; Zen, Zulhendri (TSAQOFAH, 2025)
This study aims to examine the development of creativity, talent, and learning motivation in elementary school children through the Systematic Literature Review (SLR) method by reviewing five scholarly articles published between 2019 and 2024. The study identifies strategic approaches and key factors influencing the development of children's potential within primary education settings. The analysis reveals that art-based learning, structured play activities, active parental involvement, consistent character education, and the use of engaging learning media significantly contribute to the growth of creativity, talent development, and increased student motivation. This research highlights the importance of collaboration among schools, families, and communities as a foundational element in building an educational ecosystem that supports children’s holistic development. These findings provide both conceptual and practical foundations for policymakers and educators in designing educational interventions that focus on individual potential and the psychosocial well-being of elementary school children.